In factorization by regrouping, we should remember that any regrouping of the terms in the given expression may not lead to factorization. We must observe the expression and come out with the desired regrouping by trial and error.

1) Rearranging the expression so as to form groups.

2) Find the common factors from each group.

1) 2xy + 3 + 2y + 3x

2xy + 3 + 2y + 3x

Rearranging the expression, as 2xy + 2y + 3x + 3

=

Common factor from 1st group = 2y

Common factor from 2nd group = 3

= 2y ( x + 1) + 3( x + 1)

Now there are two terms, take common binomial factor (x + 1)

= (x + 1) (2y + 3)

________________________________________________________________

2) Factorize 6xy – 4y + 6 – 9x.

6xy – 4y + 6 – 9x

Rearranging the expression, as 6xy - 9x - 4y + 6

=

Common factor from 1st group = 3x

Common factor from 2nd group = - 2

= 3x( 2y - 3) - 2( 2y - 3)

Now there are two terms, take common binomial factor (2y - 3)

= (2y - 3) (3x - 2)

________________________________________________________________

3) Factorize : 15pq + 15 + 9q + 25p

15pq + 15 + 9q + 25p

=

= 3q (5p + 3) + 5 (3 + 5p)

= 3q ( 5p + 3) + 5(5p + 3) [ use commutative property for addition]

= (5p + 3)(3q + 5)

• Factorization by common factor

• Factorization by Grouping

• Factorization using Identities

• Factorization of Cubic Polynomial

• Solved Examples on Factorization

GMAT

GRE

1st Grade

2nd Grade

3rd Grade

4th Grade

5th Grade

6th Grade

7th grade math

8th grade math

9th grade math

10th grade math

11th grade math

12th grade math

Precalculus

Worksheets

Chapter wise Test

MCQ's

Math Dictionary

Graph Dictionary

Multiplicative tables

Math Teasers

NTSE

Chinese Numbers

CBSE Sample Papers